Safety Planning With Patients Admitted to the Acute Hospital – Current Practice and Future Directions - Alice Reid; Sarah Piper; Merryn Anderson; Jessica Lynch (BJPsych Open)
Aims: Safety planning has been identified as best practice for suicide prevention and is used to support patient who are at a high risk of suicide. A key aspect of safety planning is collaborative involvement with the patient and their family/carers.